Opportunities for Heritage
IX, 421 p. 131 illus., 114 illus. in color.
Keywords: This conference proceedings, Opportunities for Heritage: Fostering Innovation, Conservation and Sustainability, is the outcome of the first international conference with the same title. The challenges in the pursuit of heritage protection and sustainable development are closely intertwined with the intricate relationship between social and economic environments, often clashing with the need to preserve heritage. It became apparent that further discussions are needed to address the pressing issues facing World Heritage around the world. This book documents the discourse on the interlinkages of heritage and sustainable development by bringing together researchers, practitioners and stakeholders from the fields of heritage at multiple levels to explore the opportunities heritage offers in implementing the UN agenda 2030, and the innovative solutions created to efficiently manage it. It highlights experiences in management including tourism management, the interlinkage between tangible and intangible heritage, living heritage, heritage digitalization and the economic opportunities provided by heritage. The work also addresses the questions of how to meet the needs and aspirations of the communities central to the sustainable management of heritage and their development aspirations. Overall, it emphasizes the importance of heritage for achieving the Sustainable Development Goals and for building peace and creating resilient communities, aiming to be a valuable resource for researchers and practitioners in the field of heritage. .